Commensurate vortex lattices and oscillation effects in superconducting Mo/Si and W/Si multilayers - Mikhailov, M.Yu.; Yuzephovich, O.I.; Bomze, Yu.V.; Buchstab, E.I.; Fogel, N.Ya. (Физика низких температур, 2005)
We report experimental results of the vortex lattice structure investigation in the artificial superconducting Mo/Si and W/Si superlattices. The resistance R and critical current Ic measurements in parallel magnetic fields have been performed as well as measurements in tilted magnetic fields. At temperatures where condition of strong layering is satisfied the dependences Ic(H||) and R(H||) reveal oscillation behavior. It is shown that the appearance of oscillations and of reentrant behavior (vanishing of resistivity in definite ranges of H||) are due to the strong intrinsic pinning and to the effect of commensurability between the vortex lattice period and multilayer wavelength. The locations of Ic(H||) and R(H||) extrema correspond to the stable states of a commensurate vortex lattice. Our experimental data are in good quantitative agreement with Ivlev, Kopnin, and Pokrovsky (IKP) theory. It is shown that the values of the commensurability fields depend exclusively on the superlattice period s and anisotropy coefficient γ and do not depend on the type of materials used for multilayer preparation. The memory effect, i.e., dependence of the oscillation pattern on the magnetic history of the sample, is observed. It is shown experimentally that the state of the vortex matter in the layered superconductors is essentially different from that of type-II superconductors with a random distribution of the pinning centers. Investigation of oscillation and reentrance behavior may be used as a new tool for vortex lattice arrangement study in layered superconductors. The essential advantage of this method is connected with its simplicity and with the possibility of using it in arbitrary large fields. Investigations of the commensurate states may be used for rather precise determination of the anisotropy coefficient γ.